Vox Populi, Vox Dei? Tacit Collusion in Politics - Christian Johansson; Anders Kärnä; Jaakko Meriläinen (Research Institute of Industrial Economics (IFN), 2021)
We study competition between political parties in repeated elections with probabilistic voting, allowing a multidimensional policy space and multiple political parties. This model entails multiple equilibria. When parties hold different opinions on some policy, they may take different policy positions that do not coincide with the median voter's preferred policy platform but converge towards it. In contrast, when parties have a mutual understanding on a particular policy, their policy positions may converge (on some dimension) but not to the median voter's preferred policy. Parties may collude with one another and take a position that differs from what the median voter prefers, despite political competition. Collusion may collapse, for instance, after the entry of a new political party. We substantiate the theoretical arguments with descriptive evidence using Swedish survey data on politicians and voters, which suggests that there is competition on some dimensions and collusion on others.
Keywords: C73; D72; P16; 330; Electoral competition; Partisan collusion; Probabilistic voting; Repeated elections; Tacit collusion